Increasing mechanical engineering students’ speaking skills using guided conversation - Syaefani Arif Romadhon; M Taufik Qurohman (Universitas Merdeka Malang, 2019)
The study aimed at describing the implementation of guided conversation at Harapan Bersama Tegal Polytechnic. The method used was a classroom action research in two cycles. The participant of the study was 30 mechanical engineering students who took English courses 2. The improvement of students’ speaking fluency was 65% in the first cycle. However, it was categorised as failed because only 13 students got a minimum score of 74 or above 74. Thus, the second cycle needs to be done. In the second cycle of learning there has been a percentage increase in the results of fluency speak 20% of the average value of 65% to 85%. All in all, students’ speaking fluency has been improved by the using Guided Conversationes.